Determinants of Religious Moderation among Islamic Preachers: A Multivariate Regression Analysis in Palembang, Indonesia - Ridwan; Suyitno; Siregar, Amri; Jamil, Syahril (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
This study was motivated by the Indonesian government’s efforts to strengthen religious moderation through Presidential Regulations No. 18 of 2020 and No. 58 of 2023, which emphasize tolerance, anti-violence, national commitment, and acceptance of local traditions. Ideally, these policies are expected to create a peaceful and inclusive society. However, intolerance and radicalism are still found in religious life, including in the preaching practices of dai. Therefore, this study examines the factors influencing dai’s understanding of religious moderation. The method used is a quantitative approach with a multivariate regression, involving 134 dai selected through purposive sampling. The results indicate that educational background (X1), social status (X6), and religious affiliation (X7) have a significant positive effect on the religious moderation of dai, while profession (X2) and place of residence (X5) show a significant negative effect. In contrast, gender (X3) and age (X4) do not significantly influence religious moderation. Since this study employed purposive sampling with a limited number of respondents, the findings are intended to provide exploratory insights into the factors influencing religious moderation among dai rather than broad generalizations to the wider population. In conclusion, the findings of this study indicate that educational background, social status, and religious affiliation significantly influence the religious moderation of dai, while profession and place of residence show a negative influence. These results imply that strengthening religious moderation among dai can be supported through educational programs and social empowerment strategies within the Palembang community.